2‐Aryl‐1H‐benz[de]isoquinolinium Ions: Cationic Dyes Displaying Mechanochromism and Crystallochromism. Issue 6 (16th March 2022) - Katayama, Koji; Matsuura, Yuka; Kitamura, Chitoshi; Nishida, Jun‐ichi; Kawase, Takeshi
Abstract: 2‐Aryl‐5, 8‐di‐ tert ‐butyl‐1 H ‐benz[ de ]isoquinolinium tetrafluoroborates were synthesized and crystalized to form yellow to orange crystals. Absorption and fluorescence maxima (λABS and λFL‐SL ) of the compounds in CH2 Cl2 depend on the electronic and steric properties of the aryl ring substituents and closely match those arising from theoretical calculations. λABS and λFL‐SL values of the compound possessing bulky 2, 6‐diisopropylphenyl substituents are the shortest among the substances because of sterically promoted retardation of conjugation between the isoquinolinium and aryl ring planes. In contrast, solid‐state fluorescence maxima (λFL‐SD ) of the compounds are not closely correlated with the electronic properties of the aryl substituents. Furthermore, one crystalline form of both the 4‐trifluoromethylphenyl and 4‐nitrophenyl derivatives exhibit mechanochromic and crystallochromic behavior reflected in absorption and fluorescence color changes. X‐ray diffraction and crystallographic analysis reveal that the solid state photophysical properties of these substances are related to different molecular stacking interactions occurring in different crystalline forms. Abstract : All in order : New 2‐aryl‐1 H ‐benz[ de ]isoquinolinium ion dyes were synthesized as stable solids. Their optical properties depend on the electronic and steric nature of aryl ring substituents. Crystals of the dyes that possess electron‐withdrawing groups (CF3 or NO2 ) as aryl substituents exhibit mechanochromism and crystallochromism, indicated by absorption and fluorescence color changes. These properties are ascribed to differences in the molecular stacking structures.